2017
DOI: 10.1080/10942912.2017.1343349
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties of partially purified polyphenol oxidase and phenolic compounds ofPrunus spinosaL. subsp.dasyphyllaas measured by HPLC-UV

Abstract: Polyphenol oxidase (PPO) enzyme was extracted from Prunus spinosa L. subsp. dasyphylla plum, partially purified by acetone precipitation, and its biochemical properties were investigated. Different substrates (p-coumaric acid, L-tyrosine, p-hydroxyphenyl propionic acid (PHPPA), catechol, 4methylcatechol (4-MTC), hydrocaffeic acid, gallic acid, quercetin, catechin, and epicatechin) were analysed to determine their affinities with Prunus spinosa PPO (PsPPO). The substrate specificity was in the following order: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…It can be seen from Figure 5 A and Table 2 that Km showed a decreasing trend and Vm showed an increasing trend as the concentration of L-DOPA increased, indicating that the binding affinity force and the catalytic rate of TE to tyrosinase increased, and the latter may be affected by the former. For (+)-catechin or (−)-epicatechin, as shown in Figure 5 B,C and Table 2 , the Km value decreased with decreasing L-DOPA concentration, indicating that (+)-catechin or (−)-epicatechin increased the binding affinity to tyrosinase as reported in the previous study [ 51 ], which may be because all (+)-catechin, (−)-epicatechin and L-DOPA can act as substrates for tyrosinase [ 13 ], and (+)-catechin or (−)-epicatechin compete with L-DOPA for the substrate binding site of tyrosinase. Meanwhile, (+)-catechin or (−)-epicatechin showed an increasing trend in the catalytic rate, consistent with the above result of TE, which further indicated that the binding affinity affects the catalytic rate of tyrosinase.…”
Section: Resultssupporting
confidence: 77%
“…It can be seen from Figure 5 A and Table 2 that Km showed a decreasing trend and Vm showed an increasing trend as the concentration of L-DOPA increased, indicating that the binding affinity force and the catalytic rate of TE to tyrosinase increased, and the latter may be affected by the former. For (+)-catechin or (−)-epicatechin, as shown in Figure 5 B,C and Table 2 , the Km value decreased with decreasing L-DOPA concentration, indicating that (+)-catechin or (−)-epicatechin increased the binding affinity to tyrosinase as reported in the previous study [ 51 ], which may be because all (+)-catechin, (−)-epicatechin and L-DOPA can act as substrates for tyrosinase [ 13 ], and (+)-catechin or (−)-epicatechin compete with L-DOPA for the substrate binding site of tyrosinase. Meanwhile, (+)-catechin or (−)-epicatechin showed an increasing trend in the catalytic rate, consistent with the above result of TE, which further indicated that the binding affinity affects the catalytic rate of tyrosinase.…”
Section: Resultssupporting
confidence: 77%
“…IC50 values were 0.011, 0.013, 0.087 mM for 4-methyl catechol, pyrogallol, catechol, respectively. In literature, it was found that ascorbic acid was the most effective inhibitory for Prunus spinosa PPO when using 4-methyl catechol as a substrate, and its IC50 value was 0.04 mM [17]. It was determined that glutathione and L-cysteine show less inhibitory effect for PPO, than the ascorbic acid.…”
Section: Resultsmentioning
confidence: 99%
“…A 20 µL sample was injected, and the flow rate was set to 1 mL/min. The detection wavelength was 280 nm [ 59 ].…”
Section: Methodsmentioning
confidence: 99%